2017
DOI: 10.1002/pat.4160
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethanes with separately tunable biodegradation behavior and mechanical properties for tissue engineering

Abstract: Two series (random and block) poly(glycolide-co-ε-caprolactone) macrodiols with various glycolide to ε-caprolactone ratios (50/50 and 30/70, R-PG50C, R-PG30C, B-PG50C, and B-PG30C) were synthesized. Next, segmented polyurethanes (PUs) were synthesized based on the synthesized macrodiols, 1,6-hexamethylene diisocyanate and 1,4-butanediol (PU-R30, PU-R50, PU-B30, and PU-B50). Effect of glycolide (G) and ε-caprolactone (C) monomers arrangement (random or block) on the PUs properties were investigated via FTIR, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…The polymers were then conjugated to bovine serum albumin (BSA), and the hydrolytic stability of the resulting conjugates was studied at neutral, acidic, and basic pH . Shokrolahi and co-workers investigated the degradation of polyurethanes consisting of glycolide or caprolactone macroblocks, which exhibited variable degradation rates depending on the macroblock composition . Chilkoti and co-workers described the preparation of water-soluble poly­(carbonate)-based polymers for protein conjugation and observed 50% polymer molecular weight loss in 12 h .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymers were then conjugated to bovine serum albumin (BSA), and the hydrolytic stability of the resulting conjugates was studied at neutral, acidic, and basic pH . Shokrolahi and co-workers investigated the degradation of polyurethanes consisting of glycolide or caprolactone macroblocks, which exhibited variable degradation rates depending on the macroblock composition . Chilkoti and co-workers described the preparation of water-soluble poly­(carbonate)-based polymers for protein conjugation and observed 50% polymer molecular weight loss in 12 h .…”
Section: Introductionmentioning
confidence: 99%
“…20 Shokrolahi and co-workers investigated the degradation of polyurethanes consisting of glycolide or caprolactone macroblocks, which exhibited variable degradation rates depending on the macroblock composition. 21 Chilkoti and co-workers described the preparation of water-soluble poly(carbonate)based polymers for protein conjugation and observed 50% polymer molecular weight loss in 12 h. 22 Additionally, the degradable monomers cyclic ketene acetals (CKAs) can be incorporated into vinyl polymers at controlled ratios to target specific hydrolytic stabilities. 23−25 We recently showed that the hydrolytic stability of fluorous 5,6-benzo-2-methylene-1,3dioxepane copolymers could be tuned by adjusting the fluorine content of the polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, PU due to its soft tissue-like properties and electroactivity can be employed as a scaffold in muscle tissue engineering [153]. Previous studies demonstrated electroactive polymers could support cell proliferation and differentiation [154].…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanical properties of the polymer did not match those required for soft tissues. So, in this present submission synthesis of a poly­(urethane-urea) (PUU) based on the same macro-diol of our previous publication, is reported, for which physiochemical and mechanical properties, as well as in vitro and in vivo biodegradation behavior are reported in comparison with its PU counterpart. To mimic a native corneal ECM, the PUU was electrospun into a scaffold to which zinc and vitamin C were added in a specially designed structure.…”
Section: Introductionmentioning
confidence: 99%